A Survey of Enhanced Device Discovery Schemes in Bluetooth Low Energy Networks. Issue 3 (4th May 2021) - Seo, Jihun; Han, Kijun
Abstract : Bluetooth Low Energy (BLE) is a popular low power wireless technology, used for short-range communication. In BLE networks, discovery process enables fast and energy-efficient communication, since all communications must involve it at the first step. For this reason, some studies have proposed novel discovery schemes to improve the performance of device discovery process. Nevertheless, literature report that provides a consolidated view are limited and insufficient. In this paper, we survey different device discovery schemes in BLE networks and discuss their advantages and limitations. The enhanced schemes are categorized into two approaches: parameter adjustment and collision avoidance approach. The first approach improves the performance by adjusting the discovery parameters according to a network situation. In the second approach, the BLE devices try to avoid the interference to reduce collisions in crowded networks.